Priorities for forestry and agroforestry policy research: report of an international workshop - Gregersen, Hans; Oram, Peter; Spears, John (International Food Policy Research Institute, 1992)
Recent intemational reviews of forestry and agroforestry research needs in developing areas (such as Bellagio II and the study conducted by the Technical Advisory Committee of the Consultative Group on Intemational Agricultural Research [CGIAR)) have placed high priority on policy research, both because of the basic importance of policy constraints in the overall course of forestry development and conservation and because of the existing lack of research in this area. In order to better identify priority issues for policy research, the Intemational Union of Forestry Research Organizations, Special Program for Developing Countries (IUFRO/SPDC), the Intemational Food Policy Research Institute (IFPRI) , and the Agency for Intemational Development (AID), in collaboration with the Food and Agriculture Organization of the United Nations (FAO) and the Forestry For Sustainable Development Program at the University of Minnesota, convened an intemational workshop on forestry and agroforestry policy research in Washington, D.C., July 9-12, 1991. It was hosted by IFPRI.